Modernizing Italy's Bankruptcy Law - Vietti, Michele (World Bank, Washington, DC, 2012)
Reforming bankruptcy laws is difficult for many reasons. First of all, attitudes in Italy toward bankruptcy make it a difficult subject to generate support for. Secondly, bankruptcy reforms are complex and lengthy. They require changes not only to the bankruptcy law but also to other important parts of the legal framework, such as the codes of civil procedures and, in the case of Italy, the penal code. Finally, they require support from those that must implement them. This paper outlines the author experience in leading the commission for the reform of the bankruptcy law and the lessons learned from it.